2014
DOI: 10.1053/j.sult.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Neurosonography

Abstract: Neonatal neurosonography is used commonly to evaluate the central nervous system in the neonatal intensive care setting. The procedure can be performed at the bedside in these critically ill patients who may suffer from hemodynamic and thermoregulatory instability and often require mechanical ventilation. This article reviews current recommendations regarding neurosonography technique, pathophysiology, and imaging of intracranial insults including hemorrhage, white matter injury, infarction, and hypoxic-ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…In contrast, coronal and sagittal images through the anterior fontanel performed with a high-frequency linear transducer (9 MHz or more) allows better resolution and more detailed visualization of structures in the near field and midline. [2][3][4][5] This technique allows optimal evaluation of the deep gray structures of the basal ganglia, lateral ventricles, and periventricular white matter and allows more detailed assessment of gray-white matter differentiation in the cortex and subcortical white matter (►Fig. 1).…”
Section: High-frequency Linear Transducermentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, coronal and sagittal images through the anterior fontanel performed with a high-frequency linear transducer (9 MHz or more) allows better resolution and more detailed visualization of structures in the near field and midline. [2][3][4][5] This technique allows optimal evaluation of the deep gray structures of the basal ganglia, lateral ventricles, and periventricular white matter and allows more detailed assessment of gray-white matter differentiation in the cortex and subcortical white matter (►Fig. 1).…”
Section: High-frequency Linear Transducermentioning
confidence: 99%
“…Over the first year of life, RI in the ACA will continue to decrease to a normal value of 0.6 in children aged 1 year and eventually reaches a normal value of 0.45 to 0.6 in children aged >2 years. 2,[7][8][9] The ACA RI will demonstrate changes in response to alterations in end-diastolic flow. For example, cerebral vascular dilatation in the setting of acute hypoxia or ischemia will result in increased end-diastolic flow generating a lower ACA RI (►Fig.…”
Section: Dopplermentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple single, and multi-centre studies reported an association between cranial US findings and adverse neurodevelopmental outcomes [93][94][95]. The strongest predictors of subsequent cerebral palsy visualised on US are ventriculomegaly and white matter echolucencies [96]. Application of advanced techniques, including the use of high-resolution linear transducers and Doppler assessment of intracranial vasculature, assist in maximizing the value of this important tool [97].…”
Section: Neuroimaging Assessment Of Pvlmentioning
confidence: 99%